2009
DOI: 10.1161/strokeaha.108.515775
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Cortical Neural Loss Associated With Cerebral Hyperperfusion and Cognitive Impairment After Carotid Endarterectomy

Abstract: Background and Purpose-Although cerebral hyperperfusion after carotid endarterectomy (CEA) often impairs cognitive function, MRI does not always demonstrate structural brain damage associated with postoperative cognitive impairment. The purpose of the present study was to determine whether postoperative cortical neural loss, which can be detected by 123 I-iomazenil single-photon emission CT, is associated with cerebral hyperperfusion after CEA and whether it correlates with postoperative cognitive impairment. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
54
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(57 citation statements)
references
References 19 publications
(32 reference statements)
3
54
0
Order By: Relevance
“…171 Therefore, in addition to the co-existing subcortical infarcts, SNL may contribute to the development of subtle poststroke cognitive impairment, depending on the degree of neuronal damage.…”
Section: Mechanismsmentioning
confidence: 99%
“…171 Therefore, in addition to the co-existing subcortical infarcts, SNL may contribute to the development of subtle poststroke cognitive impairment, depending on the degree of neuronal damage.…”
Section: Mechanismsmentioning
confidence: 99%
“…5 Moreover, several studies have found that post-CEA hyperperfusion, even when asymptomatic, causes slight but diffuse damage to the ipsilateral cerebral cortex and white matter. 3,6,7 This damage that occurs after CEA hyperperfusion is a principal cause of the postoperative cognitive impairment observed in 10% of patients following CEA. 3,6,7 Cerebrovascular autoregulatory mechanisms operate through dilation of precapillary resistance vessels that maintain CBF when reductions in cerebral perfusion pressure occur, and this is referred to as stage 1 ischemia.…”
mentioning
confidence: 99%
“…3,6,7 This damage that occurs after CEA hyperperfusion is a principal cause of the postoperative cognitive impairment observed in 10% of patients following CEA. 3,6,7 Cerebrovascular autoregulatory mechanisms operate through dilation of precapillary resistance vessels that maintain CBF when reductions in cerebral perfusion pressure occur, and this is referred to as stage 1 ischemia. 3,[8][9][10] However, the autoregulatory mechanism provides insufficient compensation for severe decreases in cerebral perfusion pressure, which then leads to decreased CBF, referred to as misery perfusion or stage 2 ischemia.…”
mentioning
confidence: 99%
“…A recent study suggested that normalization of cerebral metabolism via improvements in cerebral hemodynamics after CEA may result in cognitive improvement as well as functional recovery of the neurotransmitter system. 5) Other investigators have hypothesized that cognitive impairment after CEA may result from three possible mechanisms 2,[6][7][8][9][11][12][13]18) : cerebral hemispheric hypoperfusion during ICA clamping, intraoperative gaseous and particulate emboli from the surgical site, and postoperative cerebral hyperperfusion. The present study showed no relationship between duration of ICA clamping or new ischemic lesions on postoperative diffusion-weighted imaging and postoperative cognitive change.…”
Section: Discussionmentioning
confidence: 99%